Workshop Penggunaan Media Pembelajaran Matematika dalam Upaya untuk Meningkatkan Kompetensi Guru Sekolah Dasar Inpres Malanuza - Dhosa, Petronela Yohana (STKIP Santu Paulus Ruteng, 2018)
School action research has been implemented as a follow up from the supervision of headmaster in the state of elementary school Malanuza in the Golewa sub-district in September 2018. The purpose of this classroom action research is to improve teacher competency, especially in making mathematics learning media. Media that is designed is more oriented to objects or phenomena that are around students. The project is created in the form of workshops and was attended by all classroom teachers. The results of the workshop showed a significant increase in teacher competency from the first cycle to the second cycle. This result indicates that efforts to provide workshops for teachers are influential in improving teacher pedagogical competence.